Effects of Calcium Chloride on Shelf Life and Quality of Banana (Musa sapientum cv. Jin) (Journal of the Bangladesh Agricultural University, 2024)
Banana is a popular fruit that has been extensively cultivated in Bangladesh. However, high perishability along with very short shelf life of banana leads to immense fruit losses every year. An experiment was conducted to evaluate the effect of calcium chloride (CaCl₂) on the quality attributes and shelf life of bananas cv. Jin. The experiment was laid out in a completely randomized design with four treatments (3%, 5%, and 9% CaCl₂ concentrations and an untreated control) and three replications. The fingers of bananas were separated; randomly divided into four groups (10 fruits per group), and wetted with the CaCl₂ solution through spraying. The 5% CaCl2 treatment resulted in decreased cumulative fruit weight loss (17.85%), disease severity (50%), disease incidence (70%), and extended shelf life (5.33 days) compared to the untreated control. Banana fruit treated with 5% CaCl2 also delayed color development and maintained fruit quality (TSS, vitamin C). Therefore, a 5% CaCl2 application could be recommended for extending fruit shelf life and decreasing the decay and water loss of bananas.J Bangladesh Agril Univ 22(4): 530-538, 2024